Inclusive Employment for Persons with Disabilities Post COVID-19 in Egypt: Digitization as the Way Forward - Al Gazzaz, Rana (AUC Knowledge Fountain, 2021)
The COVID-19 pandemic has taken a heavy toll on businesses and jobs whereas many employees were furloughed and laid off. While the global pandemic had a significant negative impact worldwide, it presented a unique opportunity to revolutionize employment for persons with disabilities. Employers’ willingness to rapidly adapt to the changing work environment by transitioning businesses to remote work and flexible working schedules can facilitate an inclusive work environment for persons with disabilities, especially in communities that also face significant geographical barriers to access employment. The aim of this study is to understand the underlying challenges facing persons with disabilities in the workforce, and explore the extent COVID-19 pandemic can reshape and create new employment opportunities for people with disabilities in Egypt with the current emphasis given to digital jobs and technology. A qualitative research in the form of in-depth interviews were conducted with 9 specialists in the field of disability inclusion in Egypt and developing countries from diverse national and international professional affiliations. The research findings indicate that there is a unique opportunity that digital jobs can offer, with a potential to overcome barriers that threaten the inclusion of persons with disabilities in the workforce and exacerbate the existing inequities and disparities that existed before COVID-19. Investing in digital technology, accessibility and skills can transform the future of work for persons of disability by introducing a new era of digital employment.